Culture as renewable oil : how territory, bureaucratic power and culture coalesce in the Venezuelan Petrostate /: how territory, bureaucratic power and culture coalesce in the Venezuelan Petrostate. (2019) - Plaza-Azuaje, Penélope
No abstract available